Chlamydia trachomatis genital infection and sterility - Marques, Carlos A. S.; Menezes, Maria Luiza B. (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Being an infection that can attend an asymptomatic course, both in men and women, the Chlamydia passes unnoticed to most clinical examinations,luring infected patients into not searching medical assistance. The research on this infection is usually not consensual, not mattering if the studiedgroup is part of the average general population or consisting of a minor population that is more exposed to the disease. Adolescents and young adults, independently of socioeconomic status or racial group, have shown a greater prevalence, as in all others sexually transmitted bacterial illnesses, in function of the more intense sexual activity. Once acquired, the infection by Chlamydia trachomatis can persist for several months, resulting ina long period of dissemination. The Social American Health Association (ASHA) has advocated a routine screening of all sexually active women between 15 and 25 years, including pregnant women. The subsequent complications of a Chlamydia infection can reach great proportions when a Pelvic Inflammatory Disease (PID) occurs, causing blockage of the Fallopian tubes, pelvic adhesions, chronic pelvic pain, permanent sterility and ectopicpregnancy. This last condition is responsible for 10% of the maternal deaths in the world. In the man the uretritis and/or epididimitis resultants of this infection can narrow the urethral passage, thus diminishing fertility. In couples that search sterility treatment the detection of a Chlamydia infectionshould be taken in consideration as routine procedure, preceding invasive diagnostic methods.